What Shapes Students’ Financial Behavior? Examining Income, Financial Literacy, and Lifestyle - Retno Fidianasari; Asrid Juniar; Megi Nediawan (International Journal of Management Science and Information Technology, 2026)
Financial behavior has become increasingly important among university students as they assume greater financial independence and face more complex financial decisions. Empirical evidence concerning its determinants among students in vocational higher education institutions outside major urban areas remains limited, despite their distinct socioeconomic characteristics. The research examines the effects of income, financial literacy, and lifestyle on the financial behavior of students at Politeknik Negeri Tanah Laut. A quantitative design was employed using probability sampling with a simple random sampling technique. Data were collected from 275 active students and analyzed using PLS-SEM. The results show that income positively and significantly affects financial literacy, lifestyle, and financial behavior, while financial literacy and lifestyle also positively and significantly influence financial behavior. By integrating these variables within a single structural model, the analysis provides a more comprehensive understanding of the economic and behavioral factors underlying students’ financial behavior. The findings suggest that vocational higher education institutions should strengthen applied financial literacy programs, including budgeting, financial planning, expenditure management, and guidance on lifestyle choices aligned with students’ financial capacity. Such initiatives may promote more responsible financial behavior and support long-term financial well-being.